Deletion of the pluripotency-associated Tex19.1 gene causes activation of endogenous retroviruses and defective spermatogenesis in mice. - Rupert Ollinger; Andrew J Childs; Hannah M Burgess; Robert M Speed; Pia R Lundegaard; Nicola Reynolds; Nicola K Gray; Howard J Cooke; Ian R Adams (PLoS Genetics)
As genetic information is transmitted through successive generations, it passes between pluripotent cells in the early embryo and germ cells in the developing foetus and adult animal. Tex19.1 encodes a protein of unknown function, whose expression is restricted to germ cells and pluripotent cells. During male spermatogenesis, Tex19.1 expression is highest in mitotic spermatogonia and diminishes as these cells differentiate and progress through meiosis. In pluripotent stem cells, Tex19.1 expression is also downregulated upon differentiation. However, it is not clear whether Tex19.1 has an essential function in germ cells or pluripotent stem cells, or what that function might be. To analyse the potential role of Tex19.1 in pluripotency or germ cell function we have generated Tex19.1(-/-) knockout mice and analysed the Tex19.1(-/-) mutant phenotype. Adult Tex19.1(-/-) knockout males exhibit impaired spermatogenesis. Immunostaining and histological analysis revealed defects in meiotic chromosome synapsis, the persistence of DNA double-strand breaks during meiosis, and a loss of post-meiotic germ cells in the testis. Furthermore, expression of a class of endogenous retroviruses is upregulated during meiosis in the Tex19.1(-/-) testes. Increased transposition of endogenous retroviruses in the germline of Tex19.1(-/-) mutant mice, and the concomitant increase in DNA damage, may be sufficient to disrupt the normal processes of recombination and chromosome synapsis during meiosis and cause defects in spermatogenesis. Our results suggest that Tex19.1 is part of a specialised mechanism that operates in the germline to repress transposable genetic elements and maintain genomic stability through successive generations.